As a man eateth so is he - Barnard, Etta Marie (My University, 1902)
Introduction: “Like leaves on trees the race of man is found, Now green in youth now withering on the ground.” Man is the dominant and superior being of this great and grand universe. We have all grades and cases, all types and stamps of this human being we call man; but what of man if his food be not considered, for does not man depend entirely upon food, and the great majority upon a large amount and that of a good quality. Man could not survive long in this world if it was not for the abundant supply of food which nature has unhesitatingly given him. It might be well here to clearly explain the term food. Webster says, “Food is that which goes to support life by being received within and, assimilated by, the organism of an animal or a plant.” So we see all living things depend upon food for the life they possess. Thus we see by our definition that even the combination of H and O, which we call water, and that of O, H, and N, we call air, both the very essentials of life are foods to the living human body. Foods are divided into two classes, nitrogenous or proteid food, that is, those which contain nitrogen, and non-nitrogenous, or those which do not contain nitrogen. The latter group embraces the fats and carbohydrates which collectively are sometimes termed heat producers or respiratory foods, since by oxidation in the body they produce heat. The proteids are known as plastic foods or tissue formers since no tissue can be formed without them; but both of these groups are useful in other ways than for heat and tissue.
Citation: Barnard, Etta Marie. As a man eateth so is he. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Nutrition; Food; Proteins; Theses